INCLUSION IN HIGH SCHOOL CONTEXT: ANALYSIS OF PRODUCTIONS IN A SCIENTIFIC JOURNAL - Natália Costa de Felicio; Juliane Aparecida de Paula Perez Campos (Universidade Estadual Paulista Júlio de Mesquita Filho, 2017)
Considering the inclusion of Special Education students in High School, this study was characterized as a systematic review, which analyzed the studies published in the Ibero-American Journal of Studies in Education, between the years 2006 to 2015. The descriptors used for the search were: High School, Special Education, Inclusion, and Person with disabilities. The results showed that among the 400 papers published in all editions; only two works included the subject in question. One of them approached the inclusion of students with Down syndrome in primary and secondary education; the other discussed the teaching of Physics for deaf students. Therefore, it is necessary that scientific productions turn their attention to the modality of High School, since the Special Education students are managing to enter and have access to regular education, being necessary to analyze how is happening this process and how the school has been organized to contemplate them.